Mitogenomic analysis reveals the phylogenetic placement of monotypic Parachelon grandisquamis and distinctive structural features of control regions in mullets - Yoon, Tae-Ho; Kang, Hye-Eun; Aini, Sarifah; Wujdi, Arief; Kim, Hyun-Woo; Kundu, Shantanu (Frontiers in Marine Science, 2024)
IntroductionThe large-scale mullet, Parachelon grandisquamis (Teleostei: Mugilidae), is a monotypic species endemic to the eastern Atlantic Ocean, playing a crucial role in tropical ecosystems. Despite its ecological significance, the systematic classification of Mugilidae remains unresolved, largely due to their diverse morphology, which necessitates the integration of molecular data.MethodsThis study aimed to achieve a comprehensive molecular characterization of the species and establish its matrilineal taxonomic placement using complete mitogenome data. Next-generation sequencing was employed to generate the de novo mitogenome of P. grandisquamis, which spans 16,859 bp and includes 13 protein-coding genes (PCGs), 22 transfer RNAs, two ribosomal RNAs, and a non-coding AT-rich control region (CR).ResultsMost PCGs use ATG as the start codon, with the exception of COI, which begins with GTG. Analysis of amino acids abundance revealed high frequencies for leucine, serine, proline, threonine, and alanine with distinctive codon usage. The proportion of nonsynonymous and synonymous substitutions suggests strong purifying selection in most PCGs, except for ND4L, ND5, and ND6. Most transfer RNAs exhibited typical cloverleaf secondary structures, with the exception of tRNA-Ser1 (GCT), which lacks base pairing in the DHU arm. Mitogenome-based phylogenetic analysis using the Bayesian approach revealed that the monotypic P. grandisquamis is closely related to the genera Chelon and Planiliza within Mugilidae. Furthermore, analysis of the CRs with polymorphic nucleotides in conserved blocks provides additional insight into the development of distinct molecular markers for species identification and population structure analysis of mullets.DiscussionOverall, this study provides a comprehensive analysis of the mitogenomic structure and variation of P. grandisquamis and other mullets, confirming its maternal evolutionary relationships and offering valuable insights for advancing SNP-based species discrimination within the Mugilidae lineage.